Managing Kansas Flint Hills Grasslands - Clenton Owensby (Symphony in the Flint Hills, 2010)
The Tallgrass Prairie once encompassed some 150+ million acres in the central Great Plains area. Because of the relatively high rainfall in the region and the grassland dominance, the soils there were among the best in the world for crop production.
Keywords: grasslands; prairie; fire; ecologic; wild; nature; native; rancher; ranching; cattle; grazing; cowboy; traditional; elements; plants; grasses; animals; harvest; forage; biodiversity; climate; bluestem; indiangrass; preservation; rainfall; crops; plow; vegetation; soil; fertility; Tallgrass Prairie; burning; precipitation; maintenance